LEARNER MOTIVATION IN THE EFL CLASSROOMS: VOICES FROM A BANGLADESHI UNIVERSITY - Takad Ahmed Chowdhury; Sarbani Roy; Muhammad Kamarul Kabilan Abdullah (Indonesian Journal of Applied Linguistics)
English proficiency is considered a door opener almost in any field anywhere in the world, yet all the attempts to improve effectiveness of teaching and learning of English language in Bangladesh seem to fail over decades. Although poor learning motivation is counted as a key aspect why students do not hold their attention to their English classes and make use of their capabilities to understand and learn cognitively, there has been a very limited number of studies in Bangladeshi context to deal with this critical issue. This mixed method study attempted to identify the sources of motivation for attending English classes of the 1st year undergraduate students at a Bangladeshi university. Quantitative data was collected using two close-ended questionnaires from 50 randomly selected Bangladeshi tertiary level English language learners and 10 teachers. The student questionnaire was developed by adding three items with the ten items adapted from Clement et al. (1994) and the teachers’ questionnaire was developed and administered to follow up the findings from the student participants. For a more complete analysis, structured interviews were conducted with 10 purposively selected students. The results indicated lack of intrinsic motivation among the learners, and based on the existing literature, the study recommended the way outs to improve motivation of the non-performing learners. The recommendations included, shifting from exam-oriented assessment system, teachers’ reflection of their own teaching practices, redesigning course curricula based on learning need and learners’ expectations, ensuring easy access to the latest educational facilities, and encouraging the roles of students and their peers to develop learners’ motivation and foster their autonomous learning opportunities. Finally, the limitations are drawn and suggestions for further research are provided.